Culture of childhood playing in the schools: are children's to be left behind? - Isabel Cabrita Condessa (Universidade Federal de Santa Catarina, 2018)
The purpose of this article is to reflect on the role of the childhood play culture in the education of children, knowing that the play culture is a true immaterial heritage that is transmitted and that according to different theories have a fundamental place in childhood. In this sense, we proposed to do a mixed study based on the collection of opinions and experiences of childhood teacher's from the same region (n = 70) in order to know the value given to children's play culture. We then confronted this information with the new curricula guidelines for pre-school education, currently followed in Portugal, and we tried to give a prominent place to the play as priorities of education. From an early age, in the school, educators can propose and manage practices relevant through expressions - physical education and arts (dramatic, musical and dance, visual arts) and their integration, childhood professionals can propose some relevant practices.